Factors Predicting successful treatment outcome with novel BPaLM/BPaL regimen in individuals with drug-resistant tuberculosis: Experience From Indonesia - Arto Yuwono Soeroto; Aga Purwiga; Hendarsyah Suryadinata; Bachti Alisjahbana; Afiatin Makmun; Yana Akhmad Supriatna; Emmy Hermiyanti Pranggono; Bony Wiem Lestari (PLoS ONE, 2026)
Background and aims Drug-resistant tuberculosis (DR-TB) poses a serious challenge in Indonesia, with treatment success rates of only 50%. The BPaLM/BPaL regimen represents the latest therapeutic approach, offering shorter duration, minimal side effects, and treatment success rates of 84–90%. An operational research study conducted in Indonesia from July 2022 to March 2023 demonstrated a highly promising treatment success rate of 97.6% with the BPaLM/BPaL regimen. This study aimed to evaluate the effectiveness of the BPaLM/BPaL regimen through real-world implementation among individuals with DR-TB and identify key factors associated with successful treatment outcomes. Methods This retrospective cohort study analyzed 170 DR-TB individuals treated with BPaLM/BPaL regimens at Hasan Sadikin General Hospital, a tertiary hospital in West Java, Indonesia from January 2024 to January 2025. Data were collected from the Indonesian National DR-TB registers. A successful treatment outcome was defined as completion of treatment with bacteriological response and no evidence of treatment failure. Multivariate logistic regression was used to identify factors most associated with successful treatment outcomes and presented as adjusted odds ratios (aOR) with 95% confidence intervals. Results The study achieved an 88.8% successful treatment rate with BPaLM/BPaL regimens. Multivariate analysis revealed treatment with no missed dose events as the most important predictor for successful treatment outcome with aOR=6.42 (95%CI 1.44–28.45, p = 0.01), followed by nutritional status improvement during treatment with aOR=3.31 (95%CI 1.06–10.37, p = 0.03). A total of 132 patients (77.6%) experienced adverse effects, predominantly gastrointestinal symptoms (93.1%) and peripheral neuropathy (30.3%). Culture conversion occurred within 2 months in 95.2% of patients, with a median time to conversion of 111 days. Conclusion No missed dose events and nutritional status improvement are key predictors of successful treatment outcome. These findings support the implementation of BPaLM/BPaL regimens in Indonesia's national TB program, with emphasis on ensuring treatment adherence and nutritional status monitoring for optimal outcomes.